GENERAL LAWS AND CATEGORIES OF DEVELOPMENT. - Nuriddinov Bahodir Isobek o’g’li; Mustafayev Jafar Shomirzayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The article "General Laws and Categories of Development" outlines the processes of change and development within society. It examines the concept of "development," discussing its associated legal changes, types, and characteristics akin to those of society and nature. It delves into the evolutionary and revolutionary forms of development, their fundamental features, and their implications for society. The article discusses development processes through a system of "dialectical laws," analyzing categories of change and development within society, such as "individuality," "specificity," and "generality." It elucidates the concepts of "thesis," "antithesis," and "synthesis" as they relate to the final stages of development processes. The article is aimed at analyzing the processes of change and development within society to delineate their laws and systems.